2012
DOI: 10.1007/s00894-012-1587-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking and dynamics simulations of A.niger RNase from Aspergillus niger ATCC26550: for potential prevention of human cancer

Abstract: The aim of the present research was to study the anticancer effects of Aspergillus niger (A.niger) RNase. We found that RNase (A.niger RNase) significantly and dose dependently inhibited invasiveness of breast cancer cell line MDA MB 231 by 55 % (P<0.01) at 1 μM concentration. At a concentration of 2 μM, the anti invasive effect of the enzyme increased to 90 % (P<0.002). Keeping the aim to determine molecular level interactions (molecular simulations and protein docking) of human actin with A.niger RNase we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…However, we have shown that their actin binding capacity is essential. In line with our previous reports, we demonstrate herein that trT2-50m lacking the previously reported putative actin binding peptide [26,27] and the newly designed peptides based on hRNASET2 structure are able to bind actin and concomitantly inhibit angiogenesis. Actin binding ability was demonstrated using the immobilized actin solid phase assay and the BIAcore system.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, we have shown that their actin binding capacity is essential. In line with our previous reports, we demonstrate herein that trT2-50m lacking the previously reported putative actin binding peptide [26,27] and the newly designed peptides based on hRNASET2 structure are able to bind actin and concomitantly inhibit angiogenesis. Actin binding ability was demonstrated using the immobilized actin solid phase assay and the BIAcore system.…”
Section: Discussionsupporting
confidence: 92%
“…Based on Gundampati et al 2012, and Kumar et al 2013 [26,27] findings who claimed that they have identified the actin-binding sequence of ACTIBIND we subsequently searched for an homologous sequence in the human RNASET2 sequence and identified it. We then generated a peptide library containing 29 peptides based on this sequence and based on structural analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, docking was performed between protein and active molecules (β-Sitosterol and Calceolarioside A) using Hex server and their interaction energies were analyzed (Tables 2 and 3 ). The low energies ensured efficient docking and also revealed that the protein could form hydrogen bond networks involving various active amino acid residues [ 52 ]. Figure 11 reveals various residues that exclusively contribute towards the binding of the protein with the natural molecules.…”
Section: Discussionmentioning
confidence: 99%
“…A. niger RNase at 1 μM and 2 μM reduced invasiveness of MDA-MB 231 breast cancer cells by half and 90 %, respectively. The aforementioned information may be useful for designing new antineoplastic medications (Gundampati et al 2012;Kumar et al 2013). Hirsutellin A is a cyclizing ribonuclease with 130 amino acids from the mite fungal pathogen Hirsutella.…”
Section: Fungal Proteins and Peptides With Antitumor Activitymentioning
confidence: 99%